1995
DOI: 10.1002/mds.870100412
|View full text |Cite
|
Sign up to set email alerts
|

Reliance on advance information and movement sequencing in huntington's disease

Abstract: To identify the focus of impairment in the performance of sequential movements in Huntington's disease (HD) patients, the extent of their reliance on external advance information was examined. Twelve patients with HD and their age-matched controls performed a series of button-presses at sequential choice points along a response board. A sequential pathway was designated, and with each successive button press, advance visual information was systematically reduced to various extents in advance of each move. HD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 31 publications
(15 reference statements)
7
48
0
Order By: Relevance
“…The unstable planning of manipulative forces for HD patients when moving rhythmically hand-held objects extends previous findings of disturbed spatiotemporal behavior during bimanual activities (Hefter et al 1987;Johnson et al 2000) and sequential movements (Agostino et al 1992;Georgiou et al 1995). Overall, the present data demonstrate that regulation of movement components in unimanual and bimanual actions is disrupted in HD, resulting in modulated motor behavior.…”
Section: Modulation Of Manipulative Forces Due To Hdsupporting
confidence: 83%
“…The unstable planning of manipulative forces for HD patients when moving rhythmically hand-held objects extends previous findings of disturbed spatiotemporal behavior during bimanual activities (Hefter et al 1987;Johnson et al 2000) and sequential movements (Agostino et al 1992;Georgiou et al 1995). Overall, the present data demonstrate that regulation of movement components in unimanual and bimanual actions is disrupted in HD, resulting in modulated motor behavior.…”
Section: Modulation Of Manipulative Forces Due To Hdsupporting
confidence: 83%
“…136 A similar pattern was seen in the second task, namely, HD patients' down time and movement time were particularly prolonged at the high information reduction condition, in which information regarding the next button press was provided after the release of the previous button. 138 Finally, in the second task, HD patients had prolongation of down time and movement time comparable to those in the first task, 138 whereas PD patients showed an opposite pattern, i.e., a dramatic prolongation of movement time with relatively mild prolongation of down time. 151 Bradshaw and colleagues 138,151,153 concluded that both patient groups are deficient in sequencing motor programs effectively under conditions in which external cues are not available, as reflected in prolongation of movement preparation time (down time) and movement execution time (movement time) under these conditions.…”
Section: Motor Symptomsmentioning
confidence: 75%
“…138 Finally, in the second task, HD patients had prolongation of down time and movement time comparable to those in the first task, 138 whereas PD patients showed an opposite pattern, i.e., a dramatic prolongation of movement time with relatively mild prolongation of down time. 151 Bradshaw and colleagues 138,151,153 concluded that both patient groups are deficient in sequencing motor programs effectively under conditions in which external cues are not available, as reflected in prolongation of movement preparation time (down time) and movement execution time (movement time) under these conditions. This conclusion is consistent with the view that PD patients have difficulties in the initiation and execution of movements, particularly when no external guidance is available.…”
Section: Motor Symptomsmentioning
confidence: 75%
“…Impairments in voluntary movement appear early in HD and are often similar to those seen after damage to premotor or prefrontal cortex. HD patients show problems planning and selecting movements especially when response selection requires attention such as in sequential responses, novel contexts or when interference from competing responses is present (Agostino, Berardelli, Formica, Accornero, & Manfredi, 1992;Bradshaw et al, 1992;Curra et al, 2000;Georgiou, Bradshaw, Phillips, Chiu, & Bradshaw, 1995;Girotti, Marano, Soliveri, Geminiani, & Scigliano, 1988;Gordon, Quinn, Reilmann, & Marder, 2000;Jahanshahi, Brown, & Marsden, 1993;Phillips, Chiu, Bradshaw, & Lansek, 1995;Sprengelmeyer, Lange, & Homberg, 1995;Thompson et al, 1988).…”
Section: Sensorimotor Transformations In Hdmentioning
confidence: 99%